(untitled) (Research, Society and Development, 2024)
Currently, the use of virtual resources in the educational context has significantly expanded, being widely applied in the teaching and learning process across various courses, including higher education. This study aims to conduct an integrative review on the use of virtual objects in the teaching of medication administration. The review was based on national publications found in the LILACS and BDENF databases, from 2003 to 2017, using the descriptors "virtual object", "medication administration", and "nursing". A total of 20 articles were identified, of which six were selected for meeting the inclusion criteria: full-text articles and the use of the descriptors "medication administration" and "nursing". Although the number of articles is limited, the majority describe the development, application, and evaluation of virtual objects. The analysis showed that the use of virtual objects in teaching medication administration presents positive results and is well accepted by both teachers and students. Additionally, virtual objects have proven to be effective tools in the teaching-learning process, contributing to the strengthening of nursing students’ competencies in medication administration. This review highlights the importance of using innovative educational technologies as a valuable pedagogical strategy to enhance nursing education and practice.